Development of UTHM Pagoh Residential College Asset Declaration System 2.0 - FAKHRUDDIN, MUHAMMAD DANIAL FAKHRI; HOSNODIN, MUHAMMAD KHAIRUL NIZAM BIN; NORHISAM, MUHAMMAD EZZAT HARIZ; KASSIM@KASIM, NOORDIANA (Multidisciplinary Applied Research and Innovation, 2024)
The return and acceptance form of the residential college assets at UTHM still uses the traditional method of using paper for each student for every new semester. This method is seen as time consuming, financially inefficient and not user-friendly. This study was a continuation from the project that was done by previous final year student where feedback and comments from the previous system has been taken into consideration. This project focuses on the Pagoh Residential College and the students who live in the area. Qualitative method has been used to gain insight of the previous system developed. This system was developed based on the Agile model which involves six phases; planning, requirement analysis, design, implementation, testing, review and feedback using an Apache server, MySQL database, Visual Studio Code as the IDE, and HTML and PHP as programming languages. In the future, residential colleges and students will use this asset declaration system to reduce all problems for them from wasting time, money and energy. Improvements and additions to this project will be made if there are any necessary functionalities required.